(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The empowerment of woman in Iraq regarded as an essential part in economic development, because woman constitutes half of the society and about (49.7%) percent from the populatation So the progress of any society is correlated with the advancement of women and increasing their economic contribution and lessen the difficulties, which are restricted their abilities . The hypothesis adopted in this study states that although the efforts have been taken in the field of the empowerment of woman economically in Iraq , especially after 2003 but the building of her abilities and strengthen her contribution in development process , still needs more effective efforts from all the develoment partners’ ( state , private sector , and civilian community ) . The study divided into three chapters, The first one deals with conceptual and theoretical framwork of empowerment ot woman economically . the second chapter discuss the reality of woman from the economic point of view. while the third chapter shed light upon the future of empowerment of woman economically from the results it was appeared that it to empower women is not possible and the evidence reveals the weackness of the contribution of woman in economic activity though this ratio tends to balance with male from the size and quality, and the unemployment increases among females in compression with males. this bad situation of woman in Iraq requires resolutions to remove all the obstacles and challenges face woman . So it is important to adopte the Suggested National programme , which emphasizes upon adopting macro and sectrol policies to empower woman economically in Iraq to ensure and satisfy sustainable development in which woman becomes effective partner in building the economy and lessen the difficulties illiteracy , illness , knowledge and skill ) in order to generate positive impacts on family , community and economic and the support the path of sustainable development for ward .